Type III transforming growth factor beta receptor regulates vascular and osteoblast development during palatogenesis. Issue 2 (1st December 2014) - Hill, Cynthia R.; Jacobs, Britni H.; Brown, Christopher B.; Barnett, Joey V.; Goudy, Steven L.
<x xml:space="preserve">Abstract</x> Background: Cleft palate occurs in up to 1:1, 000 live births and is associated with mutations in multiple genes. Palatogenesis involves a complex choreography of palatal shelf elongation, elevation, and fusion. Transforming growth factor β (TGFβ) and bone morphogenetic protein 2 (BMP2) canonical signaling is required during each stage of palate development. The type III TGFβ receptor (TGFβR3) binds all three TGFβ ligands and BMP2, but its contribution to palatogenesis is unknown. Results: The role of TGFβR3 during palate formation was found to be during palatal shelf elongation and elevation. Tgfbr3−/− embryos displayed reduced palatal shelf width and height, changes in proliferation and apoptosis, and reduced vascular and osteoblast differentiation. Abnormal vascular plexus organization as well as aberrant expression of arterial (Notch1, Alk1), venous (EphB4), and lymphatic (Lyve1) markers was also observed. Decreased osteoblast differentiation factors (Runx2, alk phos, osteocalcin, col1A1, and col1A2) demonstrated poor mesenchymal cell commitment to the osteoblast lineage within the maxilla and palatal shelves in Tgfbr3−/− embryos. Additionally, in vitro bone mineralization induced by osteogenic medium (OM+BMP2) was insufficient in Tgfbr3−/− palatal mesenchyme, but mineralization was rescued by overexpression of TGFβR3. Conclusions: These data reveal a critical, previously unrecognized role for TGFβR3 in vascular and osteoblast development during palatogenesis. Developmental Dynamics, 2014. © 2014 Wiley Periodicals, Inc. Developmental Dynamics 244:122–133, 2015. © 2014 Wiley Periodicals, Inc.